The impact of sodium citrate on dialysis catheter function and frequency of catheter-related bacteriemia and haemorrhage - Maciej Szymczak (Postępy Higieny i Medycyny Doświadczalnej, 2009)
Vascular access is one of the most important problems of hemodialysis therapy. It is known that an arteriovenous fi sutla provides the best vascular access, but its creation is not always possible. Other solutions, such as the insertion of a central venous catheter, are then required. Adequate protection of such catheters by interdialytic fi ll with locking solution affects the frequency of hemodialysis-related complications. The most widespread catheter locking solution is heparin. Sodium citrate is being used more frequent recently. Available data indicate that hemorrhage is 11.9 times more frequent if the catheter locking solution is 5000 IU/ml heparin than if 40sodium citrate or 1000 IU/ml heparin is used. Other data indicate that the frequency of infection is statistically decreased when 300sodium citrate is used to fi ll the catheter instead of 5000 IU/ml heparin. Analogous data on 46.70sodium citrate are not consistent. It seems that the use of 40sodium citrate instead of 5000 IU/ml heparin does not decrease the frequency of infections. Numerous studies indicate that sodium citrate at various concentrations exerts a positive infl lence on catheter function. However, not all data are in accord. The spill of sodium citrate from the catheter to the systemic circulation is connected with a risk of adverse events. It may be dangerous if the citrate concentration is 46.720However, adequate fi lling of the catheter should prezent such events. Available data indicate that fi lling of the catheter with a solution of citrate of a concentration of no more than 300should be safe. Data on 46.70citrate are not conclusive, so precautions should be taken.